Molecular cloning of double-stranded RNA virus genomes. - Imai, M (1983)
Genome double-stranded RNAs isolated from purified human reovirus (serotype 3) and rotavirus (Wa strain) were modified at the 3' termini by addition of oligo(C) approximately 15 with T4 RNA ligase. These RNAs were transcribed into cDNA by oligo(dG)-primed reverse transcriptase and cloned after insertion into pBR322 at the Pst I site. Hybridization of plasmid-transformed Escherichia coli RR1 colonies with 32P-labeled viral genome RNAs demonstrated the presence of DNA clones representative of each of the 10 reovirus RNAs and 10 of the 11 constituent segments of the rotavirus genome. Analyses of the size and terminal nucleotide sequences of insert DNAs indicated that some clones contained a full-length copy of the virus genome segment. The complete nucleotide sequence of rotavirus genome segment 11 double-stranded RNA was obtained by using this procedure. It provides a general method for cloning double-stranded RNAs and also nonpolyadenylylated single-stranded RNAs.